Ferroelectics: Terahertz Probing Irreversible Phase Transitions Related to Polar Clusters in Bi0.5Na0.5TiO3‐Based Ferroelectric (Adv. Electron. Mater. 4/2020). (14th April 2020) - Wu, Jiyue; Sun, Wenfeng; Meng, Nan; Zhang, Hangfeng; Koval, Vladimir; Zhang, Yan; Donnan, Robert; Yang, Bin; Zhang, Dou; Yan, Haixue
Abstract : In article number 1901373, J Wu, B Yang, D Zhang, H Yan and co‐workers demonstrate the importance of terahertz (THz) technology in decoding the intrinsic structural dynamics of Bi0.5 Na0.5 TiO3 ‐based ferroelectrics. During DC‐field poling cycles, the variated dielectric response probed by reflected‐THz beam is coordinated to the permanent change of polar clusters. The evolution of perovskite unit cells symbolizes the irreversible field‐induced structural changes at the lattice scale.